Enoménoi gia mia dimokratikí vouli (ΑΚΕΛ (Progressive Party of Working People), 1981)
Shaking hands draped in banners representing different classes and social groups Original title: Ενωμένοι για μια Δημοκρατική Βουλη PO-1057